A shocker on Shock Street - Stine, R. L. (New York : Scholastic, 1995)
While Erin and her best friend Marty are visiting the new Shocker Studio Theme Park, some of the scary things which happen to them seem to be a little too real.
"An Apple paperback."
"A Parachute Press book."
grade level: 4-6
age level: 8-12
480
Accelerated Reader AR
Keywords: Amusement parks -- Juvenile fiction; Horror fiction